The Communicative Unveiling: Bridging Reputation and Reality through Dialogue in Islamic Campus Accreditation - Sazali, Hasan; Ritonga, Hasnun Jauhari; Matondang, Abdul Rahman (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study investigates organizational communication's role in achieving superior accreditation at the State Islamic University of North Sumatra (UIN-SU). The research method used is mixed, with a survey-based quantitative approach using questionnaires to collect data from UIN-SU students, lecturers, and teaching staff and a qualitative approach through interviews with universities that have achieved superior accreditation. Data were analyzed using statistical analysis techniques and path analysis with moderating variables. The results showed that UIN-SU achieved a